CMOS Op amp testing for capacitive measuring systems application - Arfah, Nurul; Alam, A. H. M. Zahirul; Khan, Sheroz (2011)
Operational amplifier (Op amp) is the most integral part of an embedded circuit building block. In this paper, the testing of an integrated Op amp suitable use for capacitance and high speed measuring system has been made. The Op amp testing (such as large signal differential transfer characteristic, frequency respond analysis, input common mode analysis, slew rate analysis) has been done using the PSpice OrCAD Version 16.0 circuit simulator and simulation results were compared with the design specification. The design of this Op amp for capacitive measuring system is making use of 0.13 μm complementary metal-oxide-semiconductor (CMOS) technology. This high speed and low power consumption system design is suitable use in a measuring system for detection a wide and lower range of capacitance.